Factors affecting the susceptibility of sensitive yeast cells to killer toxin K1 - Kurzweilová, H; Sigler, K (Folia microbiologica, 1993)
Optimum conditions for action of the killer toxin K1 on sensitive strain S. cerevisiae S6 were established. Maximum killing was reached in a very narrow pH range of 4.5-4.6. Maximum susceptibility to toxin was displayed by highly energized fresh cells from the early exponential phase in the presence of an external energy source (at least 200 mmol/L glucose). Further, maintenance of maximum membrane potential was necessary for killer action, as documented by decreasing toxin activity in the presence of increasing concentrations of KCl. The killing was strongly stimulated in the presence of millimolar concentrations of Ca2+ and Mg2+.
Keywords: energetický metabolismus; Potassium Chloride; Saccharomyces cerevisiae Proteins; Calcium; Mycotoxins; chlorid draselný; vápník; Saccharomyces cerevisiae; Hydrogen-Ion Concentration; hořčík; Magnesium; koncentrace vodíkových iontů; Energy Metabolism; antibiotická rezistence; Drug Resistance, Microbial; Saccharomyces cerevisiae - proteiny; Killer Factors, Yeast; killer faktory kvasinek; mykotoxiny